Exploring Goal–Setting Strategies of Prospective Physical Education Teachers to Maintain Academic Performance - Jusuf Blegur; Aniq Hudiyah Bil Haq; Muya Barida (STAI Hubbulwathan Duri, 2021)
Some students have successfully used goal–setting to maintain academic performance throughout their studies. Behind these successes, they implemented the strategy to the fullest, making their goals more manageable. This study explores the strategies of prospective physical education teachers using goal–setting to maintain academic performance. The research team used an exploratory qualitative approach to compare students’ experiences with good and bad academic reputations in maintaining academic performance through observation, interview, and documentation techniques. There were 11 students involved, both those with good academic reputations and vice versa. Spradley’s taxonomic analysis found that students had to reconstruct their way of learning because of traumatic experiences of academic failure and the economic limitations of the family. Goal–setting ensures that students complete their work on time and are more selective in using the clarity of information in lecturer learning designs. In addition, they reduce their learning challenges by learning and acting according to the assessment rubric, commit to each learning task and responsibility, use feedback to improve learning performance, and ensure all learning task needs by developing self–learning strategies.